Evaluasi Kinerja Keuangan Perusahaan Konstruksi Bumn Perioda 2015-2018 - Arni Utamaningsih; Chairul Muharis (Jurnal Ilmiah Rekayasa Sipil, 2020)
Performance evaluation is one of the human resource management activities that is important for achieving the goals of the construction industry company. This study aims to analyze the financial performance of BUMN industry companies that go public on the Indonesia Stock Exchange. An evaluation of financial performance was carried out on PT WaskitaKarya (Persero) Tbk, PT Wijaya Karya (Persero) Tbk, PT Adhi Karya (Persero) Tbk, and PT Pembangunan Perumahan (Persero) Tbk in the period of 2015-2018. The results showed that the profitability, solvency and liquidity tests stated that the four BUMN were able to produce large profits, with a gross profit margin that was far above the industry average. The gross profit margin value is in the range of 93.522%-101.436%, far above the industry average of 30%. However, the ability of the company to make a large gross profit is burdened by sales costs and a large interest rate, so that the net profit margin decreases, ranging from 2.848%-9.468%. The results of the evaluation of solvency and liquidity show that the four companies are inadequate in using their debts to finance all of their assets, as well as having a low ability to repay their debts. Keywords:Construction companies, Evaluation of financial performance, Profitability, Solvency, Liquidity.